Thailand : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix examines the channels of monetary policy transmission in Thailand. The main findings are that changes in monetary policy are associated with changes in real output, and that the main channel for transmission is not bank lending but asset prices. The paper takes stock of the performance of the Thai corporate sector emerging from the crisis and discusses remaining challenges and vulnerabilities. An assessment of Thailand's fiscal vulnerability is also presented.